Racismo religioso: a repercussão e os desafios da implementação da Lei 10.639/03 nas escolas públicas do município de São Paulo - Melo, Amanda Guerra (2023)
The school and its Political-Pedagogical Project (PPP) should be synonymous with knowledge, learning, respect, and democracy. However, for students who belong to religions of African origin, the school environment can sometimes be both violent and hostile. As a result of a historical process of coercion, denial, and exclusion, anchored in systemic racism, educators and students often end up reproducing symbolic and physical violence with students who practice Candomblé and Umbanda. The main goal of this research is to investigate the challenges of implementing Law 10.639/03, from the perspective of religious racism. It is based on the theoretical and conceptual subsidies of the researchers Cavalleiro (2003) who studied the intricacies and subtleties of systemic racism in relationships in an early childhood education school in the city of São Paulo, Bakke (2011) who analyzes the challenges of implementation 10.639/03 related to religions of African origins and in Nogueira (2020) with concepts related to religious racism. The research was carried out with a qualitative approach and books, scientific articles, theses, official documents published by the Municipal Secretary of Education of São Paulo, virtual journals, field research, semi-structured interviews with teachers and managers of four schools located in the Regional Directorate of Ipiranga in the city of São Paulo were used as sources. It was verified that religious racism is one of the challenges for the implementation of Law 10.639/03 and when there are teachings with pedagogical intentions aimed at solving the misconceptions of the social imaginary related to religions of African origin, there is effectively the construction of a democratic and equitable school, which wipes out the violence and empowers the students